2020
DOI: 10.1111/vru.12913
|View full text |Cite
|
Sign up to set email alerts
|

Cervical disc width index is a reliable parameter and consistent in young growing Dutch Warmblood horses

Abstract: Intervertebral disc disease, as well as the associated alteration of the radiographic intervertebral disc space width, has been reported in horses. Disc height index (DHI) has proven to be an accurate and objective parameter in other species but data related to this parameter are lacking in horses. Therefore, the aims of this retrospective longitudinal diagnostic accuracy study were (a) to evaluate the reliability of measurements within and between observers of the equine Disc Width Index (EDWI) as a parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While Der Loewe XX shows no transposition of the ventral lamina, Birkhahn XX exhibits a bi-lateral transposition to C7. The uni-and bi-lateral transposition of the ventral lamina has been described in the literature [3][4][5]8,9,[11][12][13]15,16,23,24]. The transposed ventral lamina on C7 is severely asymmetric.…”
Section: Discussionmentioning
confidence: 99%
“…While Der Loewe XX shows no transposition of the ventral lamina, Birkhahn XX exhibits a bi-lateral transposition to C7. The uni-and bi-lateral transposition of the ventral lamina has been described in the literature [3][4][5]8,9,[11][12][13]15,16,23,24]. The transposed ventral lamina on C7 is severely asymmetric.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper has proposed a cervical disc width index which takes into consideration the width of the intercentral joint relative to the length of the vertebral body. Significant mean increases in width index were seen more caudally in the cervical spine compared to the cranial aspect; they remained static up to 18 months old and did not differ significantly between sexes (Veraa et al., 2021). Standardised measurements aid the subjective evaluation of cervical radiographs, however, more research is needed to ascertain their predictive value.…”
Section: Radiographic Changes Of the Cervical Spinementioning
confidence: 99%
“…Professional personnel handling the horse can greatly assist the radiographer in ensuring the horse is evenly weight‐bearing and the spine is straight. This is important as different neck positions can affect the appearance of some structures and certain measurements, such as vertebral alignment angles and intervertebral sagittal ratios (Beccati et al., 2018; Berner et al., 2012; Veraa et al., 2021). Geometric distortion can also affect the shape of the vertebra positioned at the periphery of a radiograph (Djernæs et al., 2014).…”
Section: Acquisition Of Cervical Radiographs For a Pre‐purchase Exami...mentioning
confidence: 99%
“…In the horse, growth in the back length is as close an analogue to the sitting height and sitting height growth velocity in human studies. The comparisons between sitting height and back length are entirely conceptual, given human are bipedal and horses are quadrupedal, but the limited published data do indicate that, in the horse, growth in the wither height does provide a relatively robust proxy for growth in the spine [ 35 ]. In sheep, which are often used as an animal model for human orthopaedic research, most growth in vertebra length occurs between 3 and 6 months of age, which is analogous to the human childhood growth period between 4 years and puberty [ 36 ].…”
Section: Growth and Bone Development In The Horsementioning
confidence: 99%
“…At present, there are limited data describing appositional growth in the vertebrae of the horse. An indirect finding of a study developing a cervical disc index for horses showed there were limited changes in the size or morphology of cervical vertebrae after 18 months of age [ 35 ]. These data indicate that, in the cervical spine of the horse after 18 months old, when there is an associated attainment of a near-final wither height, there is limited growth in the horses’ vertebrae.…”
Section: Growth and Bone Development In The Horsementioning
confidence: 99%